Respostas
respondido por:
1
-x² +4 = 0
-x² = -4
x² = 4
x = +-√4
x = +-2
S = {-2,+2}
-x²+64 = 0
-x² = -64
x² = 64
x = +-√64
x = +-8
S = {-8,+8}
❤️ Bom dia ❤️
19/07
Anexos:
Pedrohe13224:
Obrigado é um bom dia para você também
respondido por:
1
- x² + 4 = 0
- x² = - 4 (-1)
x² = 4
✓x = ✓4
x = ± 2
Ou seja x1 = 2 e x2 = -2.
- x² + 64 = 0
- x² = - 64 (-1)
x² = 64
✓x = ✓64
x = ± 8
Ou seja, x1 = 8 e x2 = -8
Perguntas similares
3 anos atrás
3 anos atrás
3 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás